Pengelolaan Pendidikan Karakter Berbasis Budaya Jawa Pada Satuan Pendidikan - Nur Rulifatur Rohmah (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2021)
Character education requires the knowledge and art of managing existing resources, so that the character values that are implanted can be accepted as a whole and comprehensively, in other words so that the purpose of the education unit is to instill the values of Javanese cultural character which are beginning to be neglected, can be achieved effectively and efficient. These Javanese identic character values are integrated into the curriculum and lesson plans. By going through several stages including: learning / school planning, implementation, evaluation and development. Meanwhile, the implementation of character values based on Javanese culture involves all school members, parents and the community. In order for the cultivation of these values to be perfect. In other words, students are able to know, love and do without coercion